Embodied curriculum mapping as a foundation for critical self-reflection and culture change - Basu, Alo C. (Frontiers in Education, 2024)
This article describes a novel approach to increasing instructors' awareness of how identity, positionality, and privilege intersect with psychological, social, and cultural factors in STEM learning. Embodied curriculum mapping constitutes a qualitative method of examining teaching and learning that centers the humanity of the learner and builds empathy in instructors. It can be combined with other prevalent forms of assessment for sense of belonging such as surveys and focus groups to stimulate critical self-reflection amongst educators. Similar to autoethnographic methods, the approach prompts a bridging between the observer and the observed. Thus, it can also help build the broader identity-consciousness, of self and others, required to motivate a shift away from deficit thinking and practices in academia, which attribute racial/ethnic achievement gaps to differences in intellect, motivation, or preparation to the exclusion of sociocultural factors in the learning environment. The author's insights from this experience increased her own capacity to consider factors beyond course content that influence academic performance and common communication practices that reinforce disciplinary boundaries in introductory STEM courses. Broader adoption of this approach has the potential to expand humanistic discourse among STEM educators.